Analisis Membaca Nyaring Siswa Kelas I SD Negeri 9 Ambawang - Sari, Ratna; Setyowati, Dessy; Listiarini, Yuni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to evaluate the reading skills of grade 1 students at SD Negeri 9 Ambawang by focusing on aspects of pronunciation, intonation, volume, fluency in reading, and pauses. Considering the importance of reading aloud in the development of language skills. This study uses a descriptive qualitative approach to analyze data from the results of the reading aloud test. The data collection technique uses a reading aloud test. The analysis was carried out descriptively on all the data obtained. The results showed that students' ability to read aloud varied, with the main obstacles being fluency, intonation, and pauses. Students still have difficulties in pronunciation and adequate voice volume. These findings emphasize the need for more interactive learning methods and consistent practice to improve students' reading aloud skills. Recommendations include improved learning methods, structured exercises, the use of learning media, phonetic reinforcement and intonation, and an individualized approach to students with difficulties. Through the implementation of these recommendations, it is hoped that students' reading skills can be significantly improved, supporting the development of their literacy and language skills.